2020
DOI: 10.1002/anie.202011930
|View full text |Cite
|
Sign up to set email alerts
|

A Capacitor‐type Faradaic Junction for Direct Solar Energy Conversion and Storage

Abstract: Two-electrode solar rechargeable devices trigger intense attention due to their potential applications in solar energy conversion and storage.H owever,i nterface energy barriers lead to severe loss of output voltage and negligible dark discharge current. Therefore,external biases are required for dark discharge in these devices,l imiting their practical applications.H erein, we report an ew two-electrode device of Si/WO 3 /H 2 SO 4(aq) /C that can work without bias.The device has the highest dark output power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The fast Faradaic reaction leads to much higher charge-separation efficiency in the TiO 2 /CdS Faradaic junction. The semiconductor/semiconductor Faradaic junction is also different from a semiconductor/farador junction in previous studies and few people consider a semiconductor as a farador with redox characteristic 23 , 24 . Very importantly, we also find the characteristic of isoenergetic interfacial charge transfer in the TiO 2 /CdS Faradaic junction, which can keep high reduction potential of the electrons in the semiconductor with higher conduction band.…”
Section: Introductionmentioning
confidence: 91%
“…The fast Faradaic reaction leads to much higher charge-separation efficiency in the TiO 2 /CdS Faradaic junction. The semiconductor/semiconductor Faradaic junction is also different from a semiconductor/farador junction in previous studies and few people consider a semiconductor as a farador with redox characteristic 23 , 24 . Very importantly, we also find the characteristic of isoenergetic interfacial charge transfer in the TiO 2 /CdS Faradaic junction, which can keep high reduction potential of the electrons in the semiconductor with higher conduction band.…”
Section: Introductionmentioning
confidence: 91%
“…38,39 Additionally, as traditional solar-cell materials, Si and halide perovskite material CH 3 NH 3 PbI 3 could couple with WO 3 or NiCo 2 O 4 to output notable power energy in the dark after photocharging, respectively. 40,41…”
Section: Types Of Pes Materials and Its Design Principlesmentioning
confidence: 99%
“…9b, during photo-charging, an initial negative voltage of −0.3 V is observed in the Si/WO 3 /H 2 SO 4 (aq)/C electrode, which gradually increases to 0.7 V after 60 s of illumination. 40 Dong et al reported a photorechargeable SC with a composition of ITO BRs and P3HT semiconductor polymers. The photorechargeable SC showed an areal capacitance of 2.44 mF cm −2 at a current density of 0.02 mA cm −2 , which could be photocharged up to 0.28 V and stored the charge efficiently for several tens of seconds.…”
Section: Integrated Two-electrode Configuration Of Pes Batteriesmentioning
confidence: 99%
“…Thus, the device can output electricity for a period of time even without light irradiation 92 . In addition, metal oxides with pseudocapacitance properties can produce higher capacitance through reversible redox reactions 93–95 . For instance, the TiO 2 nanowire/NiO nanoflakes and the Si nanowire/Pt nanoparticle composites are served as photoanode and photocathode to prepare a solar‐powered device in Figure 6B.…”
Section: All‐in‐one Power Systemmentioning
confidence: 99%